Identificação dos microrganismos presentes em bebida fermentada produzida pelos índios Tapirapé - Almeida, Euziclei Gonzaga de (2005)
The Tapirapé I ndians from the tribe Tapi´itãwa produced several fermented foods including the beverage called "cauim". These amerindians live near Confresa town in the state of Mato Grosso. Several substrates can be used to prepare cauim, such as: rice, cassava, corn, peanuts among others. The fermentative process used was simple batch. Mastication of sweet potato and saliva are used as source of inoculum during the elaboration of the beverage cauim. The microbial load and their role during the fermentative process of cauim are not known, so their identification was the main aim of this study. The fermentative process of the beverage prepared with cassava and rice was evaluated with microbial and chemicals analyses. The bacteria population was of 7.9 x 109 CFU/ mL and yeasts population were of 3.2 x 104 CFU/ mL in the first hour of the fermentation. However, after 12 hours of fermentation it was observed an increased in the yeast population, which reached 6.9 x 107 CFU/ mL. From a total of 355 microorganisms isolated and identified to genus and specie level, 132 were yeasts and 223 of bacteria. Among the bacteria, 215 belonged to Gram positive group and 8 to Gram negative. The yeast genus more frequently isolated was: Candida, Cryptococcus, Lypomyces, Pichia, Debaryomyces and Trichosporon. The small number of Gram negative bacteria was represented by the following species: Enterobacter cloacae; Enterobacter agglomerans; Pseudomonas maltophilia; Serratia plymuthica. Lactobacillus, Bacillus, Corynebacterium e Paenibacillus were the genus more frequently isolated among the Gram positive bacteria. There was a dominium of Lactobacillus pentosus and Lactobacillus plantarun in all samples analyzed. The pH value varied from 3.8 to 4.9 during the fermentative process probably due to lactic acid fermentation. The chemical analyses showed that the sugars concentrations varied during the fermentative process. It was observed an increased in the concentrations of glucose, sucrose and maltose during the first 12 hours of elaboration of the beverage. Fructose concentration decreased during the fermentation process and varied from 68.68μg/mL in the samples without inoculum (SF) to 24.9μg/mL after 48 hours of fermentation. Maltose showed higher concentration after 36 hours of fermentation. There was an increase in acidity, lactic acid and acetic acid during the fermentation process.